Impact of urban and industrial features on land surface temperature: Evidences from satellite thermal indices - Portela, Carina Inácio [UNESP]; Massi, Klécia Gili [UNESP]; Rodrigues, Thanan; Alcântara, Enner [UNESP] (Elsevier, 2020)
Land surface transformations associated to the urbanization has impacted local climates and terrestrial surface energy processes. The occurrence of higher temperatures in urbanized areas when compared to rural and natural areas is called surface urban heat island (SUHI). The aim of this work was to investigate different remote sensing thermal indices and their impact in an urbanized and industrialized city in Southeast Brazil. This municipality constitutes an interesting case of middle-sized city, between two big cities, that might be currently undergoing unsustainable growth. Landsat satellite images were used to derive the thermal indices based on Land Surface Temperature (LST). The results showed that high LST values were concentrated in urban and industrial areas, with buildings, impermeable pavements and sparse vegetation. Urbanized and poorly vegetated areas showed high SUHI intensity. Vegetated areas had the best thermal comfort in town. Industries and parking lots were frequently classified as SUHI and were also considered as urban hot spots. The type of materials used in constructing these areas seems to be a reason for the higher temperatures. Further studies are needed in order to better understand the thermal conductivity of those materials and to plan how to reduce temperature in such areas.
Keywords: Land use and land cover changes; Landsat; Spectral index; Urban heat island